Microorganisms Associated With Dust on Alpine Snow - Courville, Zoe R.; Lieblappen, Ross M.; Thurston, Alison K.; Barbato, Robyn A.; Fegyveresi, John M.; Farnsworth, Lauren B.; Derry, Jeff; Jones, R. M.; Doherty, Stacey J.; Rosten, Shelby A. (Frontiers in Earth Science, 2020)
We investigated snow microstructure and microbial composition from snow samples collected from western Colorado, a region that experiences frequent dust deposition events. We developed a methodology to quantify the amount, size and location of dust particles within the snow matrix through analysis of X-ray micro-computed tomography data. Concurrently, we determined the microbial composition in sampled dust layers through DNA sequencing. We found that dust particles were generally embedded in the snow grains, with a small fraction of the dust particles’ surface area exposed to air. Microbial community composition varied more by alpine site rather than residence time of the dust within the snowpack, with the recently deposited dust layer harboring both the highest diversity and highest concentration of dust particles. The presence of microbiota in the dust-impacted snowpack has important implications for snowpack stability, melting and biogeochemistry.